Melatonin protects against ischemic stroke by modulating microglia/macrophage polarization toward anti‐inflammatory phenotype through STAT3 pathway - Liu, Zong‐Jian (CNS Neurosci Ther, 2019)
AIMS: Microglia and infiltrated macrophages play important roles in inflammatory processes after ischemic stroke. Modulating microglia/macrophage polarization from pro‐inflammatory phenotype to anti‐inflammatory state has been suggested as a potential therapeutic approach in the treatment of ischemic stroke. Melatonin has been shown to be neuroprotective in experimental stroke models. However, the effect of melatonin on microglia polarization after stroke and underlying mechanisms remain unknown. METHODS: In vivo, cerebral ischemia was induced by distal middle cerebral artery occlusion (dMCAO) in C57BL/6J mice. Melatonin was injected intraperitoneally (20 mg/kg) at 0 and 24 hours after ischemia. In vitro, the microglial cell line BV2 was stimulated to the pro‐inflammatory state with conditioned media (CM) collected from oxygen‐glucose deprivation (OGD) challenged neuronal cell line Neuro‐2a (N2a). Real‐time PCR was utilized to detect the mRNA expression of microglia phenotype markers. Activation of signal transducer and activator of transcription 3 (STAT3) pathway was determined by Western blot of phosphorylated STAT3 (pSTAT3). A neuron‐microglia co‐culture system was used to determine whether melatonin can inhibit the neurotoxic effect of pro‐inflammatory microglia to post‐OGD neurons. RESULTS: Melatonin treatment reduced brain infarct and improved neurological functions 3 days after dMCAO, which was accompanied by decreased expression of pro‐inflammatory markers and increased expression of anti‐inflammatory markers in the ischemic brain. In vitro studies confirmed that melatonin directly inhibited the pro‐inflammatory responses in BV2 cells upon exposure to OGD neuron CM. The microglia possessing pro‐inflammatory phenotype exacerbated post‐OGD N2a cells death, whereas melatonin reduced such neurotoxic effect. Further, melatonin enhanced the otherwise inhibited pSTAT3 expression in BV2 cells treated with OGD neuron CM. STAT3 blockade significantly reduced the effect of melatonin on microglial phenotype shift. Conclusion: Melatonin treatment ameliorates brain damage at least partially through shifting microglia phenotype from pro‐inflammatory to anti‐inflammatory polarity in a STAT3‐dependent manner.